Moving a step forward to promote patient safety and quality of care in Europe (Epidemiology, Biostatistics, and Public Health, 2022)
Improving safety and quality of care has always been at the heart of national, European and international policies. The premises of such concern have their roots in the times of the Greek physician Hippocrates of Cos, about the 4th century BC, with the directive primum non nocere (“first do no harm”). [...]